Albuminuria and glomerular filtration rate in obese children and adolescents - Sawamura,Luciana Satiko (2019)
Abstract Objective: To describe the frequency of albuminuria in overweight and obese children and adolescents and to relate it to the severity of obesity, pubertal staging, associated morbidities and the glomerular filtration rate. Method: Cross-sectional study including 64 overweight and obese children and adolescents between 5 and 19 years of age. Data collected: weight, height, waist circumference and systemic arterial pressure. Laboratory tests: lipid profile; glycemia and insulin, used to calculate the Homeostasis Model Assessment (HOMA-IR); C-reactive protein; glutamic-pyruvic transaminase and albuminuria in an isolated urine sample (cutoff <30 mg/g). Creatinine was used to calculate the estimated glomerular filtration rate (eGFR, mL/min/1.73 m2). Results: The mean age was 11.6 ± 3.4 years, 32 (50%) and 29 (45.3%) were male and prepubertal. Forty-six (71.9%) had severe obesity. The frequency and median (min/max) of the observed values for albuminuria (> 30 mg/g) were 14 (21.9%) and 9.4 mg/g (0.70, -300.7 mg/g). The mean eGFR was 122.9 ± 24.7 mL/min/1.73 m2. There was no significant correlation between body mass index, pubertal staging, insulin and HOMA-IR with albuminuria values and neither with eGFR. Children with albuminuria tended to have higher values of diastolic blood pressure (75.0 ± 12.2 vs. 68.1 ± 12.4, p = 0.071). Conclusion: Albuminuria, although frequent in children and adolescents with obesity, was not associated with other morbidities and the glomerular filtration rate in these patients.